2021
DOI: 10.3390/ijerph19010340
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of People with Diabetes during COVID-19 Pandemic Lockdown

Abstract: Little is known about the theoretical foundation underling the response of people with diabetes managing their everyday routines during COVID-19 pandemic lockdown. Aim: To explore the experience of people with diabetes during COVID-19 pandemic lockdown in light of the risk perception, response and behavioral change theories. Method: A qualitative descriptive design was employed, and Braun and Clark’s six step analysis were used for thematic analysis. Semi-structured interviews were conducted online using Zoom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…20%) [21] and the Middle East (n=1; 20%) [17]. [31,32,33] (Table 1 and Figure 2). In glucose management (n=4) and insulin administration (n=2), three papers used implanted phone interviews or consultations [33,34,35].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…20%) [21] and the Middle East (n=1; 20%) [17]. [31,32,33] (Table 1 and Figure 2). In glucose management (n=4) and insulin administration (n=2), three papers used implanted phone interviews or consultations [33,34,35].…”
Section: Resultsmentioning
confidence: 98%
“…Another research only mentioned online foot care consultation [36]. The Middle East (n=3; 43%) [31,33,35],…”
Section: Ehealthmentioning
confidence: 99%
“…For example, in a qualitative study conducted in China among patients with diabetes recovering from COVID-19, the authors report that the perceived barriers to the self-management of diabetes included a shortage of resources in strategies for support to meet their needs (Shi et al, 2020 ). In a study conducted in Saudi Arabia exploring the experiences of people with diabetes during the COVID-19 pandemic lockdown, researchers found that patients with diabetes expressed fears of the possibility of infection and were more inclined to seek out knowledge on strategies to remain healthy during the pandemic, underscoring the critical role CCLM models like DREAM can play during pandemic periods to be responsive to community needs (Al-Moteri et al, 2021 ). Our study findings also emphasized the need to enhance mental health support during the pandemic, which has been highlighted in a number of other settings and communities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a worldwide multicentre study revealed negative social implications in the lives of the general population [ 24 ], and a study in the US confirmed such impacts for those with T2DM compared to pre-pandemic levels [ 26 , 27 ]. In a recent qualitative study, participants with diabetes expressed fears and worries about the possibility of obtaining a COVID-19 infection that could affect their health [ 21 ]. The pandemic situation also led to behavioural changes among the majority of our participants (i.e., limitations on out-of-home leisure and social activities).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no qualitative research has yet been published to explore a comprehensive understanding of the impact of the pandemic on the lifestyle exclusively of older people with T2DM, for which any disruptive changes may affect the control of the disease and general health [ 20 ]. We found one study that explored this topic, but the authors used a mixed sample of adult patients (42 ± 12.35 years) with type 1 and 2 diabetes mellitus, and covered only the lockdown period [ 21 ]. It is important to gain a better understanding of the feelings of older people with T2DM and the ways in which they have dealt with concerns related to the management of the disease, physical exercise behaviour, health and well-being, which, in other study designs, may have remained unexplored.…”
Section: Introductionmentioning
confidence: 99%